2005
DOI: 10.1063/1.2006224
|View full text |Cite
|
Sign up to set email alerts
|

On the resonances and polarizabilities of split ring resonators

Abstract: In this paper, the behavior at resonance of split ring resonators ͑SRRs͒ and other related topologies, such as the nonbianisotropic SRR and the broadside-coupled SRR, are studied. It is shown that these structures exhibit a fundamental resonant mode ͑the quasistatic resonance͒ and other higher-order modes which are related to dynamic processes. The excitation of these modes by means of a properly polarized time varying magnetic and/or electric fields is discussed on the basis of resonator symmetries. To verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 16 publications
1
97
0
1
Order By: Relevance
“…Consequently, the double-ring SRR-C has the first and the second resonance at 800 GHz and 1,660 GHz respectively. Although numerical and experimental results [4,7,8,12] have shown that there is no resonance in the SRR-C at the same frequency as those of the other SRRs, the results do not cover a higher frequency where the resonances of each individual ring (inner and outer) occur. The SRR-C is in essence the SRR-A case with a 90 • rotation of the SRR plane while its axis is fixed.…”
Section: Discussionmentioning
confidence: 85%
“…Consequently, the double-ring SRR-C has the first and the second resonance at 800 GHz and 1,660 GHz respectively. Although numerical and experimental results [4,7,8,12] have shown that there is no resonance in the SRR-C at the same frequency as those of the other SRRs, the results do not cover a higher frequency where the resonances of each individual ring (inner and outer) occur. The SRR-C is in essence the SRR-A case with a 90 • rotation of the SRR plane while its axis is fixed.…”
Section: Discussionmentioning
confidence: 85%
“…resonant particles (a necessary condition for this is that the two metallic loops forming the SRR are tightly coupled, and hence very close [33,34]). , the impedance of this branch is found to be:…”
Section: Cpw Loaded With a Pair Of Coupled Srrsmentioning
confidence: 99%
“…The small discrepancies between simulation and measurements are attributed mainly to the inhomogeneities in the SRRs. Some papers discussed already the resonances and polarizabilities of SRRs [15], the inherent saturation of the resonant frequency when increasing the number of the rings [16], the miniaturization of the CSRRs loaded microstrip lines [17], and the group velocity in split ring resonators coupled to microstrip lines [18]. We carried out an extensive study for this kind of filter design.…”
Section: The Evolution Behind the Csrr-cpw Structurementioning
confidence: 99%
“…However, reducing the distance between the rings will be an avenue to increase the coupling and, hence, to decrease the resonance frequency. SRRs are considered as lumped or quasilumped elements in [15]. Their electrical size is λ g /8 according to the outer radius of the SRRs and their resonance frequency, where λ g is the guide wavelength.…”
Section: The Evolution Behind the Csrr-cpw Structurementioning
confidence: 99%